Tamarix and Diorhabda Leaf Beetle Interactions: Implications for Tamarix Water Use and Riparian Habitat1. (13th May 2013) - Nagler, Pamela; Glenn, Edward
Abstract Tamarix leaf beetles (Diorhabda carinulata) have been widely released on western United States rivers to control introduced shrubs in the genus Tamarix, with the goals of saving water through removal of an assumed high water‐use plant, and of improving habitat value by removing a competitor of native riparian trees. We review recent studies addressing three questions: (1) to what extent are Tamarix weakened or killed by recurrent cycles of defoliation; (2) can significant water salvage be expected from defoliation; and (3) what are the effects of defoliation on riparian ecology, particularly on avian habit? Defoliation has been patchy at many sites, and shrubs at some sites recover each year even after multiple years of defoliation. Tamarix evapotranspiration (ET) is much lower than originally assumed in estimates of potential water savings, and are the same or lower than possible replacement plants. There is concern that the endangered southwestern willow flycatcher (Empidonax trailli extimus) will be negatively affected by defoliation because the birds build nests early in the season when Tamarix is still green, but are still on their nests during the period of summer defoliation. Affected river systems will require continued monitoring and development of adaptive management practices to maintain or enhance riparian habitat values. Multiplatform remote sensing methods are playing an essential role in monitoring defoliation and rates of ET on affected river systems.